Unveiling the Complex Interplay Between Active Learning and Teacher Development: Insights from TIMSS 2022 in Georgia - Chumburidze, Manana; Setiabudi, Edy; Vassiliadou, Maria; Hasanov, Rovsen; Duangpaserth, Khamphone (Interval: Indonesian Journal of Mathematical Education, 2023)
Purpose of the study: This study investigates the relationships between active learning, teacher professional development, and mathematics achievement, leveraging data from the 2022 Trends in International Mathematics and Science Study (TIMSS) in Georgia. By focusing on a national context that has undergone significant educational reforms, this research provides a unique perspective on the synergy between instructional strategies and student outcomes. Methodology: Using a quantitative approach, data were collected from 194 teachers engaged in professional development programs through a structured questionnaire. The analysis revealed robust psychometric properties for all constructs, with moderate relationships observed between active learning and mathematics achievement. Main Findings: However, the hypothesized direct paths among active learning, teacher professional development, and student achievement were statistically significant, suggesting a more intricate interplay of contextual and mediating factors. Novelty/Originality of this study: The novelty of this study lies in its exploration of these relationships within Georgia’s educational landscape, where the intersection of professional development and active learning remains underexplored in international assessments. The findings underscore the complexity of translating pedagogical strategies into measurable improvements in student performance. Implications include the need for policymakers and educators to adopt integrated, context-sensitive approaches that address underlying factors such as teacher efficacy, classroom climate, and instructional quality. Furthermore, the study calls for future research to investigate mediating variables and longitudinal effects to uncover the mechanisms driving mathematics achievement and to inform the design of more effective educational interventions.